2012
DOI: 10.5152/eajm.2012.23
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Esmolol to Nitroglycerine in Controlling Hypotension During Nasal Surgery

Abstract: Esmolol provides hemodynamic stability and good surgical field visibility and should be considered as an alternative to nitroglycerine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…[ 16 ] Guney et al . [ 17 ] found that esmolol provides hemodynamic stability and good surgical field visibility.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] Guney et al . [ 17 ] found that esmolol provides hemodynamic stability and good surgical field visibility.…”
Section: Discussionmentioning
confidence: 99%
“…Esmolol and nitroglycerine have been frequently compared for controlled hypotension during nasal surgery. [ 8 12 ] Dexmedetomidine has also gained wide acceptance for induced hypotension because of its sedation, analgesia and anxiolysis. [ 11 13 14 ] There are no studies comparing the efficacy of these three drugs in achieving controlled hypotension.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the efficacy of esmolol for improving surgical field visibility, Guney et al [31] reported that esmolol provided hemodynamic stability and good surgical field visibility and should be considered as an alternative to nitroglycerine during nasal surgery. Also, Ibraheim et al [32] documented that esmolol and dexmedetomidine as adjuvant to anesthetic regimen, provided an effective and well-tolerated method for reduction of blood loss during scoliosis surgery, but dexmedetomidine induced prolonged extubation and recovery times.…”
Section: Resultsmentioning
confidence: 96%